Patient Influencers: The Next Frontier in Direct-to-Consumer Pharmaceutical Marketing - Erin Willis; Marjorie Delbaere (JMIR Publications, 2022)
Social media influencers are becoming an increasingly popular strategic communication tactic used across industry verticals, including entertainment, fashion, and beauty, to engage directly with consumers. Pharmaceutical companies have also recently entered the social media marketing arena and-within the bounds of governmental regulations-have found ways to build relationships directly with patients using covert persuasion tactics like partnering with social media influencers. Due to consumers' negative perceptions of pharmaceutical companies, it makes sense that new marketing tactics are being used to establish and improve relationships with consumers. Previous research well documents the ethical dilemmas of direct-to-consumer advertising, and there is recent burgeoning literature on online covert marketing tactics. The academic and medical literature, however, is behind in regard to social media influencers used in health and medicine. This paper highlights and defines terms used in industry practice, and also calls for more investigation and sets forward a research agenda. As consumers spend more time online and patients continue to consult social media for health information, it is important that this new marketing trend does not go unnoticed.